Mathematical Problem Solving Ability in Solving Sequence and Series Problems Using Polya Stages - Resiyana, Khofifah; Nugraha, Ahmad; Sakti Nugroho, Bayu (UHAMKA Press, 2023)
This study aims to determine students' mathematical solving abilities using polya stages in sequences and series material. This type of research uses qualitative research with the sample used is 6 students who have high, medium, and low mathematical abilities. Samples were taken randomly from a class X consisting of 35 students. The data collection used was a written test on sequences and series material, and interviews with 6 students. The results of this study are students who have high problem-solving abilities can solve problems using polya stages completely and sequentially, students with moderate problem-solving abilities can solve problems completely and sequentially, but there is a mistake in solving so that it is repeated. Meanwhile, students with low problem-solving abilities in solving problems do not do one final stage. From these results, it is hoped that the teacher will provide more explanation regarding the material.